2015
DOI: 10.1103/physrevc.91.034620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phonon coupling on the photon strength function

Abstract: The pygmy dipole resonance and photon strength function in stable and unstable Ni and Sn isotopes are calculated within the microscopic self-consistent version of the extended theory of finite Fermi systems, which, in addition to the standard quasiparticle random-phase approximation approach, includes phonon coupling effects. The Skyrme force SLy4 is used. A pygmy dipole resonance in 72 Ni is predicted at the mean energy of 12.4 MeV exhausting 25.7% of the total energy-weighted sum rule. The microscopically o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The microscopic calculations for isotopes 58,68,72 Ni, 116,118,122,132 Sn were used; they were taken from corresponding figures in Ref. [7,18] with energy step 0.01 MeV. The uncertainty σ exp, j for χ 2 i , Eq.…”
Section: Calculations and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microscopic calculations for isotopes 58,68,72 Ni, 116,118,122,132 Sn were used; they were taken from corresponding figures in Ref. [7,18] with energy step 0.01 MeV. The uncertainty σ exp, j for χ 2 i , Eq.…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…Different semiphenomenological approaches for the PSF of the E1 transitions were discussed in Refs. [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our works [5][6][7] it was shown that, in order to describe the observed PSF structures, it is necessary to take the phonon coupling (PC) into account in addition to the structures caused by the QRPA effects. The calculations of PSF have been performed within the selfconsistent version of the extended theory of finite fermi systems in the quasiparticle time blocking approximation (ETFFS(QTBA)) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As a new feature in these calculations, the single-particle continuum was included, thus avoiding the artificial discretization usually implied in RPA and TBA. In our previous calculations for semimagic nuclei, see, for example, [9,10,12], a discretization procedure for the single-particle continuum was used (which gave the same results within CRPA for doublemagic nuclei [9]). As the self-consistent TBA calculations of photoabsorption or PSF are rather time-consuming, we have used the corresponding results for 132 Sn from Ref.…”
Section: Introductionmentioning
confidence: 99%